Glycation of glucose sensitive lysine residues K36, K438 and K549 of albumin is associated with prediabetes - Rathore, R.; Sonwane, B. P.; Jagadeeshaprasad, M. G.; Kahar, S.; Santhakumari, B.; Unnikrishnan, A. G.; Kulkarni, Mahesh J. (Journal of Proteomics, 2019)
Prediabetes is a risk factor for the development of diabetes. Early diagnosis of prediabetes may prevent the onset and progression of diabetes and its associated complications. Therefore, this study aimed at the identification of novel markers for efficient prediction of prediabetes. In this pursuit, we have evaluated the ability of glycated peptides of albumin in predicting prediabetes. Glycated peptides of in vitro glycated albumin were characterized by data dependent acquisition and parallel reaction monitoring using LC-HRMS. Amongst 14 glycated peptides characterized in vitro, four peptides, particularly, FK(CML)DLGEENFK, K(AML)VPQVSTPTLVEVSR, K(CML)VPQVSTPTLVEVSR, and K(AML)QTALVELVK, corresponding to 3 glucose sensitive lysine residues K36, K438, and K549, respectively showed significantly higher abundance in prediabetes than control. Additionally, the abundance of three of these peptides, namely K(AML)QTALVELVK, K(CML)VPQVSTPTLVEVSR and FK(CML)DLGEENFK was >1.8-fold in prediabetes, which was significantly higher than the differences observed for FBG, PPG, and HbA1c. Further, the four glycated peptides showed a significant correlation with FBG, PPG, HbA1c, triglycerides, VLDL, and HDL. This study supports that glycated peptides of glucose sensitive lysine residues K36, K438 and K549 of albumin could be potentially useful markers for prediction of prediabetes. SIGNIFICANCE: Undiagnosed prediabetes may lead to diabetes and associated complications. This study reports targeted quantification of four glycated peptides particulary FK(CML)DLGEENFK, K(AML)VPQVSTPTLVEVSR, K(CML)VPQVSTPTLVEVSR, and K(AML)QTALVELVK, corresponding to 3 glucose sensitive lysine residues K36, K438 and K549 respectively by parallel reaction monitoring in healthy and prediabetic subjects. These peptides showed significantly higher abundance in prediabetes than healthy subjects, and showed significant correlation with various clinical parameters including FBG, PPG, HbA1c, and altered lipid profile. Therefore, together these four peptides constitute a panel of markers that can be useful for prediction of prediabetes.

Development of multiple reaction monitoring assay for quantification of carnosine in human plasma - Pandya, Vaibhav Kumar; Sonwane, Babasaheb; Rathore, Rajeshwari; Unnikrishnan, A. G.; Kumaran, Sangaralingam; Kulkarni, Mahesh J. (RSC Advances, 2020)
Carnosine, a histidine containing dipeptide, exerts beneficial effects by scavenging reactive carbonyl compounds (RCCs) that are implicated in pathogenesis of diabetes. However, the reduced carnosine levels may aggravate the severity of diabetes. The precise quantification of carnosine levels may serve as an indicator of pathophysiological state of diabetes. Therefore, we have developed a highly sensitive targeted multiple reaction monitoring (MRM) method for quantification of carnosine in human plasma samples. Various mass spectrometry parameters such as ionization of precursor, fragment abundance and stability, collision energy, tube lens offset voltage were optimized to develop a sensitive and robust assay. Using the optimized MRM assay, the lower limit of detection (LOD) and limit of quantification (LOQ) for carnosine were found to be 0.4 nM and 1.0 nM respectively. Standard curves were constructed ranging from 1.0 nM to 15.0 mu M and the levels of carnosine in mice and human plasma were determined. Further, the MRM assay was extended to study carnosine hydrolyzing activity of human carnosinases, the serum carnosinase (CN1) and the cytosolic carnosinase (CN2). CN1 showed three folds higher activity than CN2. The MRM assay developed in this study is highly sensitive and can be used for basal plasma carnosine quantification, which can be developed as a novel marker for scavenging of RCCs in diabetes.

Autoantibodies against Nε-carboxymethyl lysine and methylglyoxal modified albumin are associated with cardiovascular risk in type 2 diabetes - Patil, Yugendra R.; Tiwari, Shalbha; Momin, Abdulrahaman A.; Unnikrishnan, A. G.; Kulkarni, Mahesh J. (International Journal of Diabetes in Developing Countries, 2025)
{Background Albumin is an abundant plasma protein which gets modified with advanced glycation end products (AGEs) predominantly in diabetic condition. AGE modification induces immune response and autoantibodies are generated which play an important role in disease pathology. Objective This study aimed to illustrate the role of autoantibodies against N epsilon-carboxymethyl lysine (CML) and methylglyoxal (MG) modified albumin in diabetic cardiovascular complications. MethodsType-2 diabetes subjects were enrolled and further grouped into stress test positive or stress test negative based on treadmill stress test (TMT). Autoantibody titer was quantified by ELISA assay for CML-modified albumin (stress test positive
Keywords: AGE; Atherosclerosis; Diabetes; Glycation; Immune response; ROC

Proteome profile of stress test assessed cardiovascular disease risk-prone diabetic subjects - Patil, Yugendra R.; Tiwari, Shalbha; Unnikrishnan, A. G.; Kulkarni, Mahesh J. (Journal of Cardiovascular Translational Research, 2025)
Cardiovascular disease (CVD) is the leading cause of death in the diabetic population. There is a need for specific predictive markers to assess CVD risk. The present study explored the plasma proteome profile of treadmill test (TMT) assessed diabetic stress test positive (DSTP) and diabetic stress test negative (DSTN) subjects by performing a SWATH-MS-based label-free quantitative mass spectrometry approach to identify differentially expressed proteins (DEPs). CVD-relevant DEPs were further validated using a targeted mass spectrometry approach (MRM-HR). It was observed that CO4B, PON1 and LUM exhibited considerable differential expression in both the MS approaches, and ROC analysis showed significant AUC (0.97, 0.79 and 0.77, respectively). Overall, the present study reports these proteins as potential alternative markers for TMT in assessing CVD risk. These markers can possibly overcome the limitations of TMT with further validation in the large cohort.Graphical AbstractAn overview of experimental approaches used in the current study. The study design depicts diabetic subjects assessed for cardiovascular risk by TMT or stress test. The experimental design shows the use of the SWATH-MS approach to identify differentially expressed proteins and validate CVD-related proteins with targeted MS approaches such as MRM-HR. Finally, CO4B, PON1 and LUM exhibited significant AUC in ROC analysis, indicating their potential marker capabilities to predict CVD in diabetic subjects.
Keywords: cardiovascular disease; Diabetes; Multiple reaction monitoring; Plasma markers; Proteome profile; Quantitative mass spectrometry